FAKTOR-FAKTOR YANG MEMPENGARUHINILAI PERUSAHAAN - Muhammad Ridwan, 14.05.52.0125; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2018)
The purpose of this study is to examine and analyze the effect of managerial ownership, institutional ownership, profitability, investment decisions, firm size and capital structure on firm value. This study uses 144 sample data from manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2016 period. The analytical tool used is descriptive analysis, normality test, classic assumption test, model testing and regression test. Based on the research that has been done, it is found that managerial ownership, institutional ownership and capital structure have a positive and not significant effect on firm value, while profitability, investment decisions and firm size have a significant positive effect on firm value. Keywords: Managerial Ownership, Institutional Ownership, Profitability, Investment Decision, Company Size, Capital Structure, Firm Value